Analisis Hukum Penyebarluasan Karya Fotografi secara Non-Komersial Tanpa Izin: Studi Kasus Hotel Tentrem: Analisis Hukum Penyebarluasan Karya Fotografi secara Non-Komersial Tanpa Izin: Studi Kasus Hotel Tentrem - Herlambang, Herlambang; Hadi, Husni Abdul; Gisnan, Fayyaz Aqsadia; Mardian, Lutfi; Fatahillah, Ikhwan Aulia (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
This paper investigates the legal analysis of the land certificate issued by the National Land Agency (BPN) of Bekasi in a land dispute case that occurred in Setia Mekar, Bekasi, and evaluates the legitimacy of such administrative decision through the lens of Indonesian State Administrative Law. The research adopts a normative legal approach, utilizing statutory analysis and case study methodology. Data collection is based on a comprehensive review of legal literature and official documents, with the analysis conducted qualitatively using systematic interpretation techniques. Findings reveal that BPN Bekasi issued a certificate in Yealdi’s name without cross-checking the existence of a prior binding court ruling, thus resulting in both procedural and substantive flaws in the administrative process. The decision in question satisfies all elements of a state administrative dispute, being specific, individualized, definitive, and legally impactful. The study recommends a full-scale audit of land registration procedures, restructuring of land history verification mechanisms, and the enhancement of legal awareness among public officials and citizens to prevent the recurrence of such administrative failures.